2022
DOI: 10.1038/s41529-022-00266-w
|View full text |Cite
|
Sign up to set email alerts
|

Effects of irradiation on the mechanisms controlling the residual rate of an alumino-borosilicate glass

Abstract: The alteration of a four-oxide alumino-borosilicate glass close to International Simple Glass (ISG) was studied in Si saturation conditions at pH 3, pH 7, and pH 9 using solution and post mortem solid analyses. In particular, the study examined the impact of structural disorder on the glass alteration generated by swift heavy ion irradiation. It is shown that the pre-irradiated glass altered three to four times more than the non-irradiated glass, depending on the pH. This increased alteration can be attributed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 36 publications
10
6
0
Order By: Relevance
“…At 90 • C and pH 9, r 0 (pristine) and r 0 (irradiated) were estimated to be ∼2.46 and 14.22 ± 4.3 g m −2 d −1 , respectively. The r 0 (pristine) is in agreement with the other experimental data reported in the literature, including a recent submitted paper by Gin et al 37 The irradiated glass is estimated to dissolve ∼5.6 times faster than the pristine one. Lönartz et al 53 reported a three-time increase in the initial dissolution rate for a sodium borosilicate glass subjected to similar irradiation beams and corroded at 85 • C and pH 7.…”
Section: Initial Dissolution Rate Experimentssupporting
confidence: 90%
See 3 more Smart Citations
“…At 90 • C and pH 9, r 0 (pristine) and r 0 (irradiated) were estimated to be ∼2.46 and 14.22 ± 4.3 g m −2 d −1 , respectively. The r 0 (pristine) is in agreement with the other experimental data reported in the literature, including a recent submitted paper by Gin et al 37 The irradiated glass is estimated to dissolve ∼5.6 times faster than the pristine one. Lönartz et al 53 reported a three-time increase in the initial dissolution rate for a sodium borosilicate glass subjected to similar irradiation beams and corroded at 85 • C and pH 7.…”
Section: Initial Dissolution Rate Experimentssupporting
confidence: 90%
“…Solution analysis and ToF-SIMS profiles are in good agreement with the recent experiments conducted under similar conditions by Gin et al 37 for CJ2 glass composition. Even though the initial rate of glass dissolution, as seen in previous section, was five times faster for the irradiated CJ2 and the layer thickness was two to four times higher for irradiated CJ2, the global mechanism followed for the gel layer formation was the same, that is, partial hydrolysis and in situ reorganization.…”
Section: Ta B L Esupporting
confidence: 90%
See 2 more Smart Citations
“…Simulation results also suggest that gels tend to retain the memory of irradiation-induced disorder post hydration and continue to possess a higher reactivity. Recent experiments by Gin et al 41 on irradiated and pristine glass composition in a silica-enriched medium showed a higher decrease in the residual rate of dissolution for irradiated glass as compared to non-irradiated. They suggested higher reactivity of post irradiated glasses led to faster dissolution and redeposition; furthermore, maturation of the gel layer was also quicker, thus offering quicker passivation and a lower residual rate.…”
Section: Discussionmentioning
confidence: 95%